Urgensi pengaturan E-Voting dalam pelaksanaan pemilihan kepala daerah serentak - Mohamad Firmansyah Usman; Nirwan Junus; abdul Hamid Tome (Universitas Widya Gama Malang, 2021)
The purpose of this research is to find out and analyze the philosophical, sociological, and juridical foundations related to the arrangement of E-Voting in the simultaneous implementation of Pilkada. This type of normative research uses the Statue Approach, the Conceptual Approach. and the Comparative Approach. Based on the results and discussion, it can be concluded that: 1) in a philosophical, sociological, and juridical basis, the implementation of regional head elections by means of the E-Voting method must be in accordance with the Formation of Prevailing Laws because it has a philosophical, sociological, and juridical basis. regulations that have been issued by the government should be able to be a solution to all the cases that have occurred, including the problem of simultaneous regional head elections in several situations. This is because the existing laws and regulations are unable to answer the problems that occur. So that the KPU immediately follows up on the orders of Law Number 10 of 2016 in Article 85 paragraph 1 and Article 98 Paragraph 3 regarding E-Voting arrangements in the implementation of simultaneous regional head electionsAbstrakTujuan peneltian ini adalah untuk mengetahui dan menganalisis landasan filosofis, sosiologis, dan yuridis terkait dengan pengaturan E-Voting dalam pelaksanaan Pilkada serentak. jenis penelitian normatif dengan menggunakan Pendekatan Perundang-Undangan (Statue Approach), Pendekatan Konseptual (Conceptual Approach). dan Pendekatan Perbandingan (Comparative Approach). Berdasarkan hasil dan pembahasan, dapat disimpulkan bahwa: 1) secara landasan filosofis, sosiologis, dan yuridisnya, pelaksanaan pemilihan kepala daerah secara metode E-Voting harus berkesesuian dengan Pembentukan Peraturan Perundang-Undangan karena memiliki basis landasan filosofis, sosiologis, dan yuridis. peraturan yang telah dikeluarkan oleh pemerintah harusnya mampu menjadi solusi atas semua perkara yang terjadi, termasuk persoalan pemilihan kepala daerah serentak dibeberapa situasi. Sebab dalam ketentuan peraturan perundang-undangan yang ada tidak mampu menjawab persoalan yang terjadi. Sehingga KPU segera menindak lanjuti perintah Undang-Undang Nomor 10 Tahun 2016 pada Pasal 85 ayat 1 dan Pasal 98 Ayat 3 terkait pengaturan E-Voting dalam pelaksanaan pemilihan kepala daerah serentak.